2015
DOI: 10.3889/oamjms.2016.009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Lymphocyte Immunological Reactivity in Patients with Pleural Effusions of Different Etiology

Abstract: BACKGROUND:The proportion of T and B lymphocytes in pleural fluids and blood may point to the presence of local immunological phenomena in pleural disorders.AIM:Aim of study was to evaluate the lymphocyte phenotype and the ratio between helper (CD4+) and cytotoxic/suppressor (CD8+) lymphocytes in malignant and non-malignant effusions.MATERIAL AND METHODS:We studied 48 patients with pleural effusions. First group had 18 patients with tuberculosis pleural effusions; second group had 20 patients with malignant pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It was shown that there were more lymphocytes, but not monocytes or neutrophils, in MPE than in benign fluids. Also, lymphocytes were mostly CD4+ and the ratio CD4+/CD8+ was similar in both malignant and non-malignant pleural effusions 28,29 . Our findings of lymphocytes being the predominant cell population in MPEs are comparable with some previous studies 30 .…”
Section: Discussionmentioning
confidence: 84%
“…It was shown that there were more lymphocytes, but not monocytes or neutrophils, in MPE than in benign fluids. Also, lymphocytes were mostly CD4+ and the ratio CD4+/CD8+ was similar in both malignant and non-malignant pleural effusions 28,29 . Our findings of lymphocytes being the predominant cell population in MPEs are comparable with some previous studies 30 .…”
Section: Discussionmentioning
confidence: 84%